2020
DOI: 10.1177/2055207620905413
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone apps for cancer: A content analysis of the digital health marketplace

Abstract: Objective: The purpose of this study was to examine the state of smartphone applications for cancer intended for the general public with a focus on interactive features, content sources, and application developer affiliations. The level of health provider involvement in screening or appraising application content was also assessed.Methods: A total of 123 apps were identified for analysis from two major mobile application marketplaces (Apple iTunes ¼ 40; Google Play ¼ 83). Application characteristics were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 20 publications
1
44
0
2
Order By: Relevance
“…There are many cancer-focused mHealth apps available on the digital marketplace. 5 , 6 , 7 A prior review performed in 2014 found 166 apps targeted toward cancer patients, 7 and an update from 2015-2017 identified an additional 123 cancer-focused apps. 6 However, nearly 85% of these apps lack the ability to track symptoms, side effects, and treatments, despite patient reported outcomes (PROs) being an increasingly important component of defining patient-centered care and value.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many cancer-focused mHealth apps available on the digital marketplace. 5 , 6 , 7 A prior review performed in 2014 found 166 apps targeted toward cancer patients, 7 and an update from 2015-2017 identified an additional 123 cancer-focused apps. 6 However, nearly 85% of these apps lack the ability to track symptoms, side effects, and treatments, despite patient reported outcomes (PROs) being an increasingly important component of defining patient-centered care and value.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 A prior review performed in 2014 found 166 apps targeted toward cancer patients, 7 and an update from 2015-2017 identified an additional 123 cancer-focused apps. 6 However, nearly 85% of these apps lack the ability to track symptoms, side effects, and treatments, despite patient reported outcomes (PROs) being an increasingly important component of defining patient-centered care and value. 6 , 7 Indeed, determining ways to integrate real-time collection and evaluation of PROs in a user-friendly and easily integrated electronic format is essential for optimal patient-provider communication and accurate symptom tracking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, of the over 325,000 health-related apps available [ 26 ], over 500 are skin related, with 90 providing self-surveillance and diagnosis [ 27 ]. Evaluation of six apps for skin cancer diagnosis has been conducted in high-income countries with discouraging results [ 28 ], and content analysis of 123 apps demonstrated that all were in need of improvement [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of smartphones and technological advances has given rise to a range of applications for medical and healthcare purposes. The field of oncology is no exception, with applications being made available for, amongst others, education, treatment information, prevention and early detection [1]. A large proportion of the applications claiming to provide the opportunity for early detection are active within the field of skin cancer.…”
mentioning
confidence: 99%